Field performance of hermaphrodite papaya plants obtained through molecular selection and micropropagation - Araya Valverde, Emanuel (2019)
Most commercial papaya varieties segregate hermaphrodite and female plants. Growers normally select hermaphrodite plants in the field, due to market preferences. This requires planting multiple plants per site and later thinning of the females, distinguished by flower bud inspection. Micropropagation or the use of molecular markers are two possibilities to grow only hermaphrodite plants. Under the tropical conditions of this study, the field performance of hermaphrodite papaya plants developed by both of these methods was described. Moreover, a multiplex qPCR reaction was optimized. Hermaphrodite seedlings selected by molecular markers and plants obtained by micropropagation, had a lower slenderness ratio and initiated fruit production at a lower height than those selected by the conventional practice of the orchard. An analysis of flower types between the sex determination methods indicated that growing one hermaphrodite papaya plant per hole reduces the percentage of female-sterile flowers, resulting in fruit set at a lower trunk height and higher yields.